IMPLEMENTASI PROGRAM PENGEMBANGAN SUPERVISI PENDIDIKAN UNTUK PENGEMBANGAN PROFESIONAL GURU DI SMP NEGERI 1 MALIKU - Khairunnisa; Apriani, Tanti; Metroyadi; Sakka, Ambo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the educational supervision development program in improving teacher professional development at SMP Negeri 1 Maliku. This research uses a descriptive qualitative approach to understand the supervision process comprehensively and contextually. The study was conducted from March to April 2026, with the school principal as the main subject. Data were collected through interviews, observations, and documentation. The results show that the implementation of supervision has shifted from a conventional system to a more structured and technology-based system through online applications. The supervision process includes planning, classroom observation, reflection, feedback, and continuous evaluation. Supervision is more oriented toward coaching rather than assessment, although it is integrated with performance appraisal systems. The findings also indicate that supervision has a positive impact on teacher professionalism, particularly in improving teaching methods and learning planning. However, several challenges were identified, including differences in perception, limited number of supervisors, and lack of formal training. Overall, the implementation of supervision is considered quite effective but still requires improvement in mentoring, training, and system understanding to optimize teacher professional development.